2019
DOI: 10.1039/c9nr04647j
|View full text |Cite
|
Sign up to set email alerts
|

Halide-assisted metal ion reduction: emergent effects of dilute chloride, bromide, and iodide in nanoparticle synthesis

Abstract: Halide ions catalytically enhance metal ion reduction rate, providing a versatile design tool for controlling metal nanoparticle growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 35 publications
2
30
0
1
Order By: Relevance
“…Results on silicon revealed that two mechanisms were at play: oxidation of the nanocube corners and gold reduction at the surface. Slight modification of the welding procedure, by performing the reaction at pH 1 (to promote oxidation) and introducing micromolar concentrations of NaBr (to enhance (100) facets reactivity [ 48 ] ) enabled gold nanocube epitaxy on all substrates, including PDMS, transforming the welding procedure developed on silicon into a general solution route toward continuous monocrystalline nanostructures of arbitrary shape (Figure 2b). Figure 2c illustrates a periodic array of gold nanoantennas (with an aspect ratio of 2) obtained via nanocube epitaxy on a PDMS substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results on silicon revealed that two mechanisms were at play: oxidation of the nanocube corners and gold reduction at the surface. Slight modification of the welding procedure, by performing the reaction at pH 1 (to promote oxidation) and introducing micromolar concentrations of NaBr (to enhance (100) facets reactivity [ 48 ] ) enabled gold nanocube epitaxy on all substrates, including PDMS, transforming the welding procedure developed on silicon into a general solution route toward continuous monocrystalline nanostructures of arbitrary shape (Figure 2b). Figure 2c illustrates a periodic array of gold nanoantennas (with an aspect ratio of 2) obtained via nanocube epitaxy on a PDMS substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Bromine ions are commonly used in nanocube synthesis to direct crystal growth because they bind to (100) facets, reducing their surface energy and growth rate. [ 28,48 ]…”
Section: Resultsmentioning
confidence: 99%
“…When regarding the inorganic and organic parts as a donor‐acceptor system and the anchor group as bridging ligand, parallels can be drawn with Taube's concept of inner and outer sphere electron transfer: [118] To achieve a highly coupled through‐bond inner sphere transfer, a non‐innocent ligand is required. This can either be an atomic ligand [119] or a conjugated group, preferably with covalent character [102] . Outer sphere electron transfer on the other hand occurs through space, and is dependent on spatial proximity and driving force, that is, potential difference, [120] thereby accounting for the length dependence in NC systems coupled by insulating ligands [106] …”
Section: Organic Componentsmentioning
confidence: 99%
“…Innensphären‐Elektronentransfers ziehen: [118] Um einen hochgradig gekoppelten Innensphärentransfer über Bindungen zu erreichen, ist ein “nicht‐unschuldiger” (non‐innocent) Ligand erforderlich. Dies kann entweder ein atomarer Ligand [119] oder eine konjugierte Gruppe sein, vorzugsweise mit kovalentem Charakter [102] . Der Außensphären‐Elektronentransfer hingegen erfolgt durch den Raum und ist abhängig von der räumlichen Nähe.…”
Section: Organische Komponentenunclassified